2007
DOI: 10.1109/mwsym.2007.380357
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Broadband Negative Group Delay Active Circuits

Abstract: International audienceThis paper deals with the design and synthesis of active circuits able to simultaneously produce negative group delay and gain at microwave frequencies or for baseband signals. Analytical equations show that the proposed topology meets these objectives while also satisfying active device requirements. Then, a synthesis approach is extracted and applied to design a two stage microwave circuit, further validated by experimental results. This method is extended to the design of a four-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 9 publications
4
54
0
Order By: Relevance
“…Since NGD occurs at the range of frequencies where the absorption or the attenuation is maximum [2], conventionally, in the microwave regime, bandstop structures are used to realize NGD circuitry. Based on either series or shunt resonators, many active and passive NGD circuitries have been proposed and demonstrated with or without tunability [6]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since NGD occurs at the range of frequencies where the absorption or the attenuation is maximum [2], conventionally, in the microwave regime, bandstop structures are used to realize NGD circuitry. Based on either series or shunt resonators, many active and passive NGD circuitries have been proposed and demonstrated with or without tunability [6]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…In microwave regime, conventionally, bandstop structures are used to realize NGD circuitry; based on either series or shunt RLC resonators, many active and passive NGD circuitries have been proposed and demonstrated with or without tunability [2]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that certain passive [1][2][3][4][5][6][7][8] and active [9][10][11][12][13][14][15][16][17][18] circuits are susceptible to exhibit the negative group delay (NGD) function at low-and RF-/microwavefrequencies. Theoretical and experimental analyses confirm that this innovative physical function allows to generate an output signal with wave fronts propagating in advance of its input under certain conditions [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%